Motion of charged particles in a spacetime of a five dimensional rotating black hole in a magnetic field - Kaya, R. (SPRINGER/PLENUM PUBLISHERS, 2007)
We study the effect of an external magnetic field on the stability of circular motion around a five dimensional Myers-Perry metric. Using the Hamilton-Jacobi formalism we derive the effective potential for the radial motion of charged particles around a five dimensional rotating black hole in a uniform magnetic field. We show that there are stable circular orbits around a five dimensional rotating black hole immersed in a uniform magnetic field.
Keywords: black holes; classical theories of gravity; Astronomy & Astrophysics; Physics